2017
DOI: 10.1186/s12885-017-3554-4
|View full text |Cite
|
Sign up to set email alerts
|

Differences in elongation of very long chain fatty acids and fatty acid metabolism between triple-negative and hormone receptor-positive breast cancer

Abstract: BackgroundTriple-negative breast cancer (TN) is more aggressive than other subtypes of breast cancer and has a lower survival rate. Furthermore, detailed biological information about the disease is lacking. This study investigated characteristics of metabolic pathways in TN.MethodsWe performed the metabolome analysis of 74 breast cancer tissues and the corresponding normal breast tissues using LC/MS. Furthermore, we classified the breast cancer tissues into ER-positive, PgR-positive, HER2-negative breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 44 publications
2
60
0
Order By: Relevance
“…Elongation of saturated FAs is mediated by ELOVL 1-7 [58]. ELOVL 1 and 6 mRNA levels were up-regulated in TNBC when compared with the luminal A subtype and up-regulated in both compared with normal tissue [59]. This suggests that the increase in PC � C-40 in TNBC cell lines may be explained by an increased production of long-chain FAs.…”
Section: Increased Phosphatidylcholine Synthesis In Triple Negative Bmentioning
confidence: 92%
“…Elongation of saturated FAs is mediated by ELOVL 1-7 [58]. ELOVL 1 and 6 mRNA levels were up-regulated in TNBC when compared with the luminal A subtype and up-regulated in both compared with normal tissue [59]. This suggests that the increase in PC � C-40 in TNBC cell lines may be explained by an increased production of long-chain FAs.…”
Section: Increased Phosphatidylcholine Synthesis In Triple Negative Bmentioning
confidence: 92%
“…The RB model 7, however, on an average, had 27% reduced flux through synthesis of only C22:4 and C22:5 fatty acids. Chain length of very long-chain fatty acids has been reported to be used for differentiating between cancer types [63]. Furthermore, metabolic profiling of retinoblastomas revealed that certain RB groups had increased lipids as compared to other RB groups that exhibited very low lipid concentrations [14].…”
Section: Long-chain Fatty Acid Synthesismentioning
confidence: 99%
“…5D; Table 3) included: (1) YTA7/ATAD2/ATAD2B , which localizes to chromatin and regulates histone gene expression. ATAD2 overexpression portends poor prognosis in gastric, colorectal, cervical, hepatocellular carcinoma, lung, and breast cancer, and thus overexpression sensitivity could represent the potential to target a driver gene [119-125]; (2) PIF1 / PIF1 , a DNA helicase, which is involved in telomere regulation and is required during oncogenic stress [113]; (3) RPS1B/RPS3A , which is a small subunit ribosomal protein that is overexpressed in hepatitis B associated hepatocellular carcinoma and non-small cell lung cancer [114,115]; (4) LEO1/LEO1 , which associates with the RNA polymerase II and acts as an oncogene in acute myelogenous leukemia [156]; (5) ELO3/ELOVL1/ELOVL2/ ELOVL4/ELOVL6 , which constitutes a family of fatty acid elongases that function in sphingolipid biosynthesis, among which ELOVL1 is overexpressed in breast and colorectal cancer tissue [107,108], ELOVL2 is upregulated in hepatocellular carcinoma [109], and ELOVL6 is overexpressed and associated with poor prognosis in liver and breast cancer [110,111] ; (6) MDL2/ABCB10 , which is a mitochondrial inner membrane ATP-binding cassette protein and is upregulated in breast cancer [112]; (7) CPR3/PPIA , which is a mitochondrial cyclophilin that is upregulated in lung cancer, esophageal, and pancreatic cancer [104-106]; and (8) SAC3/MCM3AP/SAC3D1 , which is a nuclear pore-associated protein functioning in transcription and mRNA export, with MCM3AP being upregulated in glioma cells [116], while SAC3D1 is upregulated in cervical cancer and hepatocellular carcinoma [117,118]. Yeast gene deletion suppression together with overexpression sensitivity of human homologs in cancer reveals potential therapeutic vulnerabilities that can be further explored in both systems.…”
Section: Resultsmentioning
confidence: 99%